TRANSIENT PRESSURE WAVES IN HILLSLOPES - Waswa, George W. (My University, 2013)
Previous studies found that during a rainfall event, pre-event water, which exists in the catchment before the event, may appear in significant amounts in the stream stormflow hydrograph. Pre-event water is predominantly groundwater. Among the mechanisms that have been proposed to explain the rapid mobilization of pre-event water from hillslopes are: (1) groundwater ridging (GWR) i.e. the rapid rise of a water table in environments, where the capillary fringe, or the zone of tension saturation, is very close to the ground surface and (2) the Lisse Effect (LE) i.e. the rapid response of a groundwater level to pressurized pore air in the unsaturated zone. Published literature explains that GWR is caused by the application of a small amount of water on the ground surface. On the LE, it is explained that pressurized pore air acts at the water table, resulting in a rapid rise of the water level in a well, screened below the water table. These explanations are insufficient on the physical processes involved in GWR and the LE. The objectives of this study were: (1) to use the commonly observed catchment hydrological processes i.e. tensiometric pore water pressure, shallow groundwater levels, rainfall data and the hydraulic properties of soils, to quantify and describe the physical processes involved in GWR and the LE mechanisms; (2) to perform laboratory experiments, in order to understand the physical processes involved in the LE; and (3) to develop a mathematical theory that can describe the physical processes in the LE. Results indicated that GWR and the LE are caused by the addition (elevation) of potential energy in water within the capillary fringe. In GWR, the additional energy is from the intense rainfall. In the LE, the additional energy is from compressed pore air in the unsaturated zone. In both mechanisms, the added energy diffuses through the capillary fringe, as a downward pressure wave, releasing the tension forces in water. As soon as the downward pressure wave-front arrives at the water table, the water table begins to ascend, as an upward pressure wave. The ascending water table steepens the hydraulic gradient, which results in the rapid groundwater fluxes, without the recharge of the water table by the infiltration profile.
Keywords: Capillary fringe; Compressed pore air; Diffusion equation; Groundwater fluxes